2010
DOI: 10.1029/2009gl041681
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of subsurface interfaces in lunar maria by the LRS/SELENE sounding radar: Influence of mineralogical composition

Abstract: The Lunar Radar Sounder (LRS) of the SELENE mission has detected horizontal subsurface features at depths of a few hundreds of meters within all major lunar maria. We have mapped these features at global scale and found a heterogeneous geographical distribution, which correlates negatively with the maps of TiO2 and FeO obtained from UV‐VIS measurements by the Clementine probe. High concentration of ilmenite (FeTiO3) in the basaltic mare lava can explain this correlation, this mineral being a strong absorber fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…The Lunar Radar Sounder (with 60 m wavelength) onboard the Kaguya mission also detected subsurface interfaces in Mare Serenitatis, Mare Crisium, Mare Smythii, Mare Nectaris, Mare Humorum, Mare Imbrium, and Oceanus Procellarum, which might represent the interface between the basalt flows and underlying crust. However, the thicknesses from Kaguya appear to be thinner than from the Apollo experiment, and it is uncertain if the Kaguya radar sounder detected the mare‐highland interface or just a shallower interface between two lava flows of differing ages [ Ono et al , ; Pommerol et al , ; Oshigami et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The Lunar Radar Sounder (with 60 m wavelength) onboard the Kaguya mission also detected subsurface interfaces in Mare Serenitatis, Mare Crisium, Mare Smythii, Mare Nectaris, Mare Humorum, Mare Imbrium, and Oceanus Procellarum, which might represent the interface between the basalt flows and underlying crust. However, the thicknesses from Kaguya appear to be thinner than from the Apollo experiment, and it is uncertain if the Kaguya radar sounder detected the mare‐highland interface or just a shallower interface between two lava flows of differing ages [ Ono et al , ; Pommerol et al , ; Oshigami et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the geological structures in the lunar maria can be directly investigated using the observation data of the Lunar Radar Sounder (LRS) onboard Kaguya (SELENE), which detected echoes from layers at depths of several hundred meters [ Ono et al ., ; Oshigami et al ., ; Pommerol et al ., ]. LRS was a chirp radar using a wavelength of ~60 m to detect echoes from subsurface discontinuities, where the permittivity changes abruptly [ Ono and Oya , ].…”
Section: Introductionmentioning
confidence: 99%
“…They also pointed out that clear subsurface echoes were well found in the old-age area; the surface ages of most of the area are older than 3.4 billion years. As for the inhomogeneity of the clear subsurface echoes, Pommerol et al (2010) made another suggestion that there was clear anticorrelation between the observation points of clear subsurface echoes and TiO 2 -rich area. Olhoeft and Strangway (1975) reported that loss tangent of the surface media depends on the abundance of ilmenite.…”
Section: Initial Results Of Radar Sounder Observationsmentioning
confidence: 97%